2020
DOI: 10.1186/s40249-020-00765-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of HIV self-testing among female sex workers in China: implications for expanding HIV screening

Abstract: Background Human immunodeficiency virus (HIV) self-testing may help improve test uptake among female sex workers. China has implemented many HIV self-testing programs among men who have sex with men, creating an opportunity for promotion among female sex workers. However, there is a limited literature on examining HIV self-testing among female sex workers. This study aimed to examine HIV self-testing experiences and its determinants among female sex workers in China. Methods A venue-based, cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…In our study, HIV testing was associated with a history of self-reported STIs, which has also been reported in previous studies [ 36 ]. The reason may be that the Chinese government implemented provider-initiated HIV/syphilis testing and counselling (PITC) services to expand HIV testing for potential HIV-positive individuals in STD clinics.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, HIV testing was associated with a history of self-reported STIs, which has also been reported in previous studies [ 36 ]. The reason may be that the Chinese government implemented provider-initiated HIV/syphilis testing and counselling (PITC) services to expand HIV testing for potential HIV-positive individuals in STD clinics.…”
Section: Discussionsupporting
confidence: 89%
“…A total of 23 studies investigated the proportion of those who previously self-tested. Only 2 studies reported on the prevalence of HIVST used in the past in HIV high-risk populations other than men who have sex with men (MSM) [ 43 , 51 ], with the lowest proportion of those who previously self-tested being the male clients of female sex workers (2.6%), as reported by Lau et al [ 51 ]. The highest prevalence of HIVST use in the past was observed in the study by Jin et al [ 62 ], that is, 74.5% in HIV-negative MSM.…”
Section: Resultsmentioning
confidence: 99%
“…HIV testing is a key entry point for HIV prevention and treatment programs. Previous studies have shown that HIVST may enhance HIV testing uptake, increase HIV testing frequency, and limit potential harm among key populations [ 9 , 43 ]. According to Figueroa et al [ 65 ], when using HIV rapid diagnostic tests with high accuracy, those who self-test may obtain results similar to those obtained by health care workers in health care settings.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, few studies have assessed frequencies of testing, and instead a lot has been reported on the recent testing outcome (26). With the introduction of self-testing, studies have reported a potential benefit of increasing the frequency of HIV testing among FSWs (35,36) , this study therefore highlights a need for programs and studies to actively track complementary HIV testing outcomes including accessibility to HIV testing services, willingness to test and frequency of HIV testing among FSWs so that the data can be used for evidence based service delivery.…”
Section: Discussionmentioning
confidence: 99%